Assuring the integrity of offshore carbon dioxide storage. (September 2022) - Connelly, D.P.; Bull, J.M.; Flohr, A.; Schaap, A.; Koopmans, D.; Blackford, J.C.; White, P.R.; James, R.H.; Pearce, C.; Lichtschlag, A.; Achterberg, E.P.; de Beer, D.; et al.
Abstract: Carbon capture and storage is a key mitigation strategy proposed for keeping the global temperature rise below 1.5 °C. Offshore storage can provide up to 13% of the global CO2 reduction required to achieve the Intergovernmental Panel on Climate Change goals. The public must be assured that potential leakages from storage reservoirs can be detected and that therefore the CO2 is safely contained. We conducted a controlled release of 675 kg CO2 within sediments at 120 m water depth, to simulate a leak and test novel detection, quantification and attribution approaches. We show that even at a very low release rate (6 kg day −1 ), CO2 can be detected within sediments and in the water column. Alongside detection we show the fluxes of both dissolved and gaseous CO2 can be quantified. The CO2 source was verified using natural and added tracers. The experiment demonstrates that existing technologies and techniques can detect, attribute and quantify any escape of CO2 from sub-seabed reservoirs as required for public assurance, regulatory oversight and emissions trading schemes. Highlights: An artificial CO2 release demonstrated MMV techniques for offshore CCS. Detection of leakage was demonstrated using acoustic, chemical and physical approaches. Attribution of leakage was proved possible using artificial and natural tracer compounds. Leakage quantification was possible using approaches not previously applied to CCS studies. Non-catastrophic leaks were detected at levels below those that would cause environmental harm.